Electroanalysis Applied to Compatibility and Stability Assays of Drugs: Carvedilol Study Case - Murilo Ferreira de Carvalho; Luane Ferreira Garcia; Isaac Yves Lopes de Macedo; Ricardo Neves Marreto; Mayk Teles de Oliveira; Renê Oliveira do Couto; Carlos Eduardo Peixoto da Cunha; Karla Carneiro de Siqueira Leite; Kênnia Rocha Rezende; Fabio Bahls Machado; Vernon Somerset; Eric de Souza Gil (MDPI AG, 2020)
Carvedilol (CRV) is a non-selective blocker of α and β adrenergic receptors, which has been extensively used for the treatment of hypertension and congestive heart failure. Owing to its poor biopharmaceutical properties, CRV has been incorporated into different types of drug delivery systems and this necessitates the importance of investigating their compatibility and stability. In this sense, we have investigated the applicability of several electroanalytical tools to assess CRV compatibility with lipid excipients. Voltammetric and electrochemical impedance spectroscopy techniques were used to evaluate the redox behavior of CRV and lipid excipients. Results showed that Plurol® isostearic, liquid excipient, and stearic acid presented the greatest anode peak potential variation, and these were considered suitable excipients for CRV formulation. CRV showed the highest stability at room temperature and at 50 °C when mixed with stearic acid (7% w/w). The results also provided evidence that electrochemical methods might be feasible to complement standard stability/compatibility studies related to redox reactions.